Comparative Analysis of The Performance of Syariah Mutual Funds With Conventional Funds - Mujahid Mujahid; Rachmat Sugeng; Yasir Yasir; Syamsul Riyadi; Karima Karima (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
In carrying out investment activities, it is to seek a profit and expect the invested funds to be stored safely and can be retrieved quickly if they want to be needed again, Mutual funds are a new investment vehicle that has minimized risks because the funds that have been collected can be invested in various types of investment vehicles, such as bonds, stocks and money market instruments. In this study aims to determine the "comparative analysis of the performance of Islamic mutual funds with conventional mutual funds through equity mutual funds and fixed income mutual funds.